2002
DOI: 10.1007/s00775-002-0379-6
|View full text |Cite
|
Sign up to set email alerts
|

The H2 sensor of Ralstonia eutropha: biochemical and spectroscopic analysis of mutant proteins modified at a conserved glutamine residue close to the [NiFe] active site

Abstract: [NiFe] hydrogenases contain a highly conserved histidine residue close to the [NiFe] active site which is altered by a glutamine residue in the H(2)-sensing [NiFe] hydrogenases. In this study, we exchanged the respective glutamine residue of the H(2) sensor (RH) of Ralstonia eutropha, Q67 of the RH large subunit HoxC, by histidine, asparagine and glutamate. The replacement by histidine and asparagine resulted in slightly unstable RH proteins which were hardly affected in their regulatory and enzymatic properti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 44 publications
6
75
0
Order By: Relevance
“…An exception is the Q67H variant of the RH from R. eutropha, for which Buhrke et al 29 found e 2 Qq/h = 1.79 MHz and η = 0.53, values that are closer to the ones obtained here. On the basis of DFT calculations, a shorter distance of N τ to the S of the spincarrying cysteine residue was discussed as a possible reason, in line with the rather large observed isotropic hyperfine coupling.…”
Section: ■ Discussionsupporting
confidence: 83%
“…An exception is the Q67H variant of the RH from R. eutropha, for which Buhrke et al 29 found e 2 Qq/h = 1.79 MHz and η = 0.53, values that are closer to the ones obtained here. On the basis of DFT calculations, a shorter distance of N τ to the S of the spincarrying cysteine residue was discussed as a possible reason, in line with the rather large observed isotropic hyperfine coupling.…”
Section: ■ Discussionsupporting
confidence: 83%
“…Exploring a hypothesis that the atypical behavior results from restricted access of the larger diatomic compounds due to a difference in the amino acid residues that line the gas-access tunnel of regular H 2 ases, as opposed to the sensors, Friedrich, Lenz, and co-workers prepared mutants of the RH enzyme in which the larger residues found along the RH tunnel were exchanged by smaller ones. [25] Such mutants with expanded cavities were found to lose activity in the presence of O 2 , supporting the conclusion that the sensors were designed to block and prevent O 2 access to the active site. A further extensive specific amino acid mutation study by Liebgott [26] So now, the issue Reproduced from ref.…”
mentioning
confidence: 67%
“…[124] support of this assignment, similar studies on the Ni-C state of the H 2 -sensing hydrogenase from R. eutropha, in which this residue is replaced by a glutamate, showed no such 14 N signals. [136] A site-directed mutation of this glutamate to a histidine residue recovered the resonances of this 14 N nucleus in the ESEEM spectra, as observed in D. gigas and D. vulgaris hydrogenases. [51,101] A more detailed pulsed EPR and HYSCORE examination fully supported the nitrogen coordination of the active site in D. vulgaris MF [137] by His88, using natural abundance and 15 N-enriched histidine samples as well as a comparison with DFT calculations.…”
Section: Interactions Of the Active Site With The Protein Surroundingmentioning
confidence: 93%